PENGOPTIMALAN THROUGHPUT dan KESAMARATAAN INDEKS FAIRNESS PADA JARINGAN NIRKABEL CODE DIVISION MULTIPLE ACCESS (CDMA) - Ningsih, Yuli Kurnia; Wiryanto, Andy (Jurnal Teknik Elektro, 2006)
Currently, Code Division Multiple Access (CDMA) technology was not only utilize for voicecommunication, but for data communication too. TCP throughput get important role in thiscase. Frequently, performance and unfairness index throughput which is accepted user area serious problem in the CDMA network. This paper describe about solution of unfairnessthroughputâs problem. From simulation results, index fairness every user approach one (1)with let more RTT connection so long and power control. Thatâs mean throughput every userhave been optimal.Keywords: throughput, TCP, Round Trip Times (RTT), Power control